On whole-slide imagery and computational pathology in medical diagnosis - Канцемал, А. О. (ХНУРЕ, 2023)
This work is devoted to exploring the phenomena of whole-slide imagery and computational pathology in medical diagnosis. In addition, we assess CLAM – one of the methods of computational pathology, aimed to process whole-slide tissue scans – as a way of addressing the important whole-slide imagery processing difficulties.